Le morte Darthur : the original text edited from the Winchester manuscript and Caxton's Morte Darthur - Malory, Thomas, Sir, active 15th century; Field, P. J. C. (Rochester, NY : D.S. Brewer, 2017)
"This definitive original spelling text edition of Malory's classic text has been described as a 'major event in the long history of Malory scholarship', and hailed as 'our standard critical edition of Malory'."--Publisher description.
Includes bibliographical references and index.
Mode of access: Internet.
Keywords: Arthur, -- King; Arthur, -- King -- Fiction; Knights and knighthood; Arthurian romances; Knights and knighthood -- Great Britain -- Fiction; Arthurian romances; Great Britain; Fiction